스마트폰 블루투스를 이용한 승강기 호출 지능형 IoT 시스템 제안 - 김시연(Si Yeon Kim); 노순국(Sun-Kuk Noh) (스마트미디어저널, 2024)
The Internet of Things, which began by connecting sensors through a network, is developing into an intelligent IoT by combining it with artificial intelligence technology. Elevators are essential for high-rise buildings in the city, and elevators move from floor to floor and perform the functions of transporting goods and moving users. It is necessary to provide safe and convenient services for elevator users in high-rise buildings or special environments (hospitals, etc.). In an environment where rapid patient transportation is important, such as large hospitals, there is a problem that hospital staff and the general public often use the elevator for patients. In particular, when moving patients where golden time is important, the waiting time to board the elevator is a major hindrance. In order to solve this problem, this study proposes an intelligent IoT system for elevator calling using smartphone Bluetooth. First, we experimented with the elevator calling IoT system using smartphone Bluetooth, and as a result of the experiment, it was confirmed that it can authenticate elevator users and reduce unnecessary waiting time for boarding. In addition, we propose an intelligent IoT system that connects with intelligent IoT. 센서들을 네트워크로 연결하면서 시작된 사물인터넷은 인공지능 기술과 결합하면서 지능형 IoT로 발전되고 있다. 도심 고층 건물들은 승강기가 필수적으로 설치되고, 승강기는 층을 이동하며 화물 운반과 사용자 이동의 기능을 수행한다. 고층 건물이나 특수 환경(병원 등)의 승강기 사용자에게 안전하고 편리한 서비스를 제공해야 한다. 대형 병원과 같이 신속한 환자 운송이 중요한 환경에서 병원 직원 및 환자용 승강기에 일반인들도 수시로 이용하는 문제점이 존재한다. 특히, 골든 타임이 중요한 환자 이동 시 승강기를 탑승하기 위한 대기 시간은 큰 방해 요소이다. 이러한 문제를 해결하기 위해서 본 연구에서 스마트폰 블루투스를 이용하여 승강기 호출 지능형 IoT 시스템을 제안한다. 먼저 스마트폰 블루투스를 이용하여 승강기 호출 IoT 시스템을 실험하고, 실험결과, 승강기 사용자의 인증 및 불필요한 탑승 대기시간을 감소시킬 수 있음을 확인하였다. 또한 지능형 IoT로 연계하는 승강기 호출 지능형 IoT 시스템을 제안한다.